On feebly continuous functions and feebly compact space (مجلة ديالى للبحوث الانسانية, 2022)
The main purpose of this paper is to study a new kinds of continuous functions called feebly continuous function ,  f *eebly continuous  function and f **eebly continuous functions and study some of their characterizations and proving number of theorems , corollaries , propositions , remarks , examples and  their relationships with continuous functions .Also we will introduce      a new concept of compact spaces called feebly–compact spaces           (f- compact space) and study the relationship of it with usual compact spaces .